Ermittlung eines Skelettierungsverfahrens zur Konvertierung von Topologieoptimierungsergebnissen - Mayer, Johannes; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
By showing where to place material in a specified design space, the continuous topology optimization is very useful in product development of structural loaded components. However the optimizations design proposal is far from being a parametric CAD-model. Instead it usually consists of a tesselated surface, that has to be re-engineered. As this is often done manually, it takes a lot of time and expert knowledge. Curve skeleton algorithms have proven their ability to support the restructuring of truss-like design proposals by providing references for construction elements. To investigate a similar design concept for general optimization results, showing truss-like structures as well as surface-like sections, the suitability of surface skeletons for topology reconstruction is examined.<br
Keywords: Computational Geometry; Topology Optimization; Medial Axis Transform; Surface Skeleton